Urgensi Bahasa Arab Bagi Hafizh Al-Qur’an - Noza Aflisia (Institut Agama Islam Negeri (IAIN) Curup, 2016)
Hafiz Al-Quran is a title given to someone who has memorized the Qur'an. Memorizing the Qur'an is an ability to learn and try to save the verses of Allah in his memory so when it wanted to say, it could instantly remembered by someone. To get the title of Hafiz Al-Quran is not easy and practical, but requires a good strategy, namely: sincere intention, determination, away from immoral, utilizing childhood and youth, prayer lavatory, multiply prayers, determine methods, improve reading, understand the meaning of the verse, report the rote, multiply the murattal hearing, repeating the rote, involving all the senses, memorize to the teacher, using one type of Mushaf Al-Quran, the right time, pay attention at the verses which are similar and do not left behind. Allah has promised to people who memorize it about the advantages and virtues of the Quran. Hafiz Al-Quran is Allah's family, the most noble, honor the Hafiz Quran means glorify of Allah, the heart of Qur'an’s memorizer will not tortured, cherished by the Prophet, may intercede to families, will wear a crown of honor, the parents will get special reward when their children is Qur'an’s memorizer, will keep high position in paradise. A Hafiz Al-Quran is in need Arabic to continue and maintain rote memorization, because if he has the ability to speak Arabic, a Hafiz will recall the memory through stories or verses themes that are memorized. Arabic make the Qur’an memorizers easier to memorize verses of the Qur'an, because by understanding the meaning of the Qur'an, it is easier for the memorizers to apply them in everyday life. Further, by understanding the Arabic language, one will not lost in the reading.